Treatment of Klebsiella mastitis in a Crossbred Jersey Cow - Venkatesan, M; Pradheep, N; Jayalakshmi, K; Yogeshpriya, S; Veeraselvam, M; Premalatha, N (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A four years old primiparous Jersey crossbreed cow of one-month lactating was presented with swelling of right fore quarter and straw yellow milk. The grade of CMT test on milk was (+++). Klebsiella spp., isolation done by bacteriological culture of milk using blood agar. Plasma fibrinogen and plasma protein ratio was used as an indicator for assessment of recovery. Inj.Gentamicin 5 mg /kg IV & 10 ml intramammary along with supportive therapies were given for 5 days. 12thday post treatment the milk quality drastically improved.